Environmental factors affecting patterns of distribution and co-occurrence of two competing raptor species - M. Brambilla; E. Bassi; CECI, CHIARA; D. Rubolini (Ibis, 2010)
Habitat selection is a complex process, that is affected by several factors, including habitat characteristics, environmental conditions, and both intra- and interspecific interactions. We analysed habitat preferences of two top avian predators, Peregrine Falcon Falco peregrinus, a medium-sized diurnal raptor, and Eagle Owl Bubo bubo, a large nocturnal raptor. These two species are known to compete for preferred nest-sites, and proximity to cliffs with Eagle Owls may reduce Peregrine breeding output through predation of young Falcons. We investigated the environmental factors affecting occurrence and coexistence of the two species and the potential role of habitat suitability in favouring co-occurrence in 3519 km2 of the central pre-Alps of Italy, where the two species breed on cliffs and sometimes co-occur on the same cliff. Peregrines settled on long, steep and favourably orientated cliffs in woodland landscapes close to urban areas. Eagle Owls settled on topographically similar cliffs, but in lower rainfall areas compared with cliffs occupied by Peregrines and cliffs unoccupied by either species. Sites where the two species co-occurred were characterized by more horizontally extended cliffs compared with sites of exclusive occurrence of each species. An analysis of relative habitat suitability revealed that sites where the two species co-occurred had the highest predicted probability of occupancy for both species, suggesting that those sites should be regarded as high-quality sites. Breeding productivity of Eagle Owls was negatively affected by the co-occurrence of Peregrines, whereas the effect of Eagle Owl proximity on Peregrine productivity varied according to cliff suitability for the Peregrines. Habitat selection had fitness consequences for Eagle Owls because breeding productivity increased with cliff length. Environmental conditions, particularly climatic factors, could allow the widespread coexistence of these competing raptors at the landscape scale, whereas at the local scale co-occurrence could ...